Pengaruh Latihan Aktivitas Maze Dan Target Terhadap Keterampilan Teknik Dasar Sepakbola SSB Tunas Jaya Kota Jambi - ADHE SAPUTRA (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
Based on researcher observation inthe field, showedthat there was stilla lack ofbasicfootballskills in studentsSSBTunasJayaCity ofJambi. This research aimed to observe the effects of maze exerciseactivity and targetactivitytowardbasic technique skill offootball. The hyphotesis of the research were (1)mazeexercise activity gaveinfluence tobasictechnique skillof football. (2) Target exercise activity gave influence to basic technique skill of football. (3) Target exercise activity gave influence to basictechnique skill of football.The population of the researchwasfootballplayerswho joinedonTunasJaya club in Jambi. The active player was about 80 persons.The samplesof the research werejuniorgroupDamount 30persons. It chose because junior group D has 3 month in SSBTunasJayaandtheydidn’t have more skill infootball. The sampling techniquewas done by usingrandom samplingtechniques. The division ofthe sampleinto groupswas done by usingordinally matchingpairing. In techniques of data collection, the researcher usedfootballskill tests toaged10-12 years. And for the technique of data analysis, the researcher used t testconductedby ttest formula thatrelated to t sample.The results of the research showed that(1)maze exerciseactivitycanincreasethe basic techniques skill of footballinSSBTunasJayaJambi. (2) Target exerciseactivitycan increasethe basictechniques skillof football inSSBTunasJayaJambi. (3) There was no different between maze exercise activity and target activity in increasing basic technique skill of football inSSBTunasJayaJambi. Kata Kunci : Latihan Aktivitas Maze, Latihan Ativitas Target, Keterampilan Sepakbola